Contemporary Approaches in Stuttering Therapy - Peins, Maryann (Little, Brown, 1984)
Keywords: Stuttering; Treatment; Speech therapy; Treatment; Stuttering in children; dept.cmd; faculty_collection

Instrumentation for monitoring lingual pressure in vibrotactile research - Kingsbury, Gary D; Sansone, E Frank; Kelly, Dan H (Review of Scientific Instruments, 1984)
In order to avoid obtaining variable measurement data it is critical to control pressure applied to the tongue by positioning clamps used in lingual vibrotactile research. A pressure sensing plate, associated electronics, and procedures are described which, when employed with positioning clamps in current use, will permit monitoring lingual pressure during vibrotactile investigations.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/114-981-553-013-894 tex.type: [object Object]
Keywords: dept.cmd